The knots of narrative. Contemporaneity and its relation to history. (15th May 2015) - Crossland, Zoë
<x content-type="archive" xml:space="preserve">Abstract</x> In this wonderfully rich and thought-provoking article, Gavin Lucas exhorts us to write about archaeology in the mode of the contemporary. This is to attend to the shifting interplay between past, present and future, undertaken through a focus on the relations between objects, in contrast to the impoverished concern with succession and order that a notion of chronological contemporaneity imposes. His paper undertakes the useful task of disentangling concepts around time and contemporaneity, and raises a number of interesting questions. Here, I would like to discuss two of the most compelling contributions of Lucas's paper: the foregrounding of modes of persistence and of consociality, both of which I would like to explore by reflecting on my experiences of historical narrative and alternate temporalities in the history of highland Madagascar. The issue of persistence introduces the question of historical privilege – that is, how do some things persist while others fall to dust? And how is that persistence recognized and maintained? This same question of recognition (and misrecognition) is also at the heart of consociality; how are consociates acknowledged as contemporaneous, and what room is there for refusal?